Educational management in kindergarten - Bescu, Monica-Mihaela (Journal of Community Positive Practices, 2019)
The article addresses the issues of educational management in kindergarten and of educational leadership. These two concepts are very important and a lot of researchers are interested to find more information about. We are interested to discover the importance of the activity of a manager in a kindergarten and how this activity influences the quality of education provided there. In the education system in Romania, we have kindergartens that have legal personality and kindergartens that are structures of another kindergarten or another school. Also, there are kindergartens from rural or urban areas. In this article, we propose an approach to the issue of educational management in order to be able to find out to what extent a kindergarten management can influence the work of teachers and all staff in the education unit to achieve quality education.